IPO UNDERPRICING AND FINANCIAL ANALYSTS’ FORECAST ACCURACY IN POLAND - Pomykalski, Przemysław; Domagalski, Maciej (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
We review the theory and evidence on IPO activity and underpricing focusing on the Warsaw Stock Exchange and confirm that many IPO phenomena in Poland are not stationary. Focusing on the behavioural reasons for underpricing, we investigate the accuracy of analysts’ valuations made prior to initial public offerings. Using a unique set of data, we find a disappointing lack of accuracy, not only in the results of valuations but also in the underlying forecasts of revenues.